2019
DOI: 10.1002/joc.6400
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting drought impacts on the start of phenological growing season in Northern China during 1982–2015

Abstract: Drought is a widely occurring extreme climatic event that may have various effects on vegetation phenology and activity. The change of the start of the phenological growing season (SOS) is one key mechanism for ecosystem responses to droughts yet remain unknown at large scale. This study used abnormal changes in the ratio of reference evapotranspiration (ETO) and precipitation (P) to detect the pre‐season (defined as the 3 months before the growing season) monthly drought during 1982–2015. After that, the pre‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 87 publications
3
12
0
Order By: Relevance
“…We hypothesized that rice in drier regions was more vulnerable than in wetter regions during extremely hot conditions. Because high temperatures contributed to greater vapor pressure deficits and increased water demand in drier areas than in wetter areas, transplantation was further prevented since the early growth stage was susceptible to water deficiency (H. Deng et al., 2020; Yuan et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that rice in drier regions was more vulnerable than in wetter regions during extremely hot conditions. Because high temperatures contributed to greater vapor pressure deficits and increased water demand in drier areas than in wetter areas, transplantation was further prevented since the early growth stage was susceptible to water deficiency (H. Deng et al., 2020; Yuan et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous evaluations show that longer extension of LOS significantly relates to advanced SOS [33][34][35]. However, several studies have exhibited the contrast results that the SOS shows a slower advanced rate or delayed after 2000 due to drought and deficiency of soil moisture [36,37], and climate extremes [38]. Further analysis is necessary to ascertain this trend at a regional scale because the interannual variability of LSP is changing with the warming climate.…”
Section: Introductionmentioning
confidence: 98%
“…Recent desert-oasis transition zones in the basin of NWC showed a reduction in area in response to the warming climate and human activities [ 35 ]. Deng et al [ 36 ] found that the start time for the phenology growing season was 0.66–3.45 d later than that of previous years under drought condition. In addition to damaging ecosystems, the variations in vegetation carbon sinks and sources can exert growing pressures on economic development and social stability.…”
Section: Introductionmentioning
confidence: 99%